Analysis of the Instruction Language in the Arabic Language Textbook of the Ministry of Religion for Class VII - Adira, Wafa' Rizqiyya; Muhajir, Muhajir (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
This research aimed to analyze the language of instruction used in class VII Arabic textbooks published by the Ministry of Religion. The language used for instruction in class VII Arabic textbooks should be easily understood by students, so it is necessary to analyze it in order to evaluate it if there are any discrepancies in it. This research used qualitative methods with a library research approach. The result explained that there are 115 questions instructions in the Arabic textbooks for class VII MTs published by the Ministry of Religion in 2020 which is divided into 6 chapters. In chapter I there were 23 question instructions, chapter II 19 question instructions, chapter III 23 question instructions, chapter IV 16 question instructions, chapter V 18 question instructions, and chapter VI question instructions. Instruction language that complies with the 1st criteria is 99,1%, 2nd and 3rd criteria are 100%, 4th criteria is 57,4%, and 5th criteria is 18,3%. So that this book is feasible to be used as Arabic teaching material by evaluating several points to comply with the feasibility of teaching materials based on Rusydi Ahmad Thu’aimah’s standards, especially in the theory of instruction language.